2020
DOI: 10.1002/cncr.33245
|View full text |Cite
|
Sign up to set email alerts
|

Moving through cancer: Setting the agenda to make exercise standard in oncology practice

Abstract: LAY SUMMARY International evidence‐based guidelines support the prescription of exercise for all individuals living with and beyond cancer. This article describes the agenda of the newly formed Moving Through Cancer initiative, which has a primary objective of making exercise standard practice in oncology by 2029.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 27 publications
2
59
0
2
Order By: Relevance
“…Creating landscapes that promote exercise and active transport such as biking and walking is particularly important to cancer patients. Many clinical trials have shown the positive effects that walking and physical activity can have on quality of life and survival time in cancer patients [ 90 ], and are known to reduce risk of colorectal cancer development [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Creating landscapes that promote exercise and active transport such as biking and walking is particularly important to cancer patients. Many clinical trials have shown the positive effects that walking and physical activity can have on quality of life and survival time in cancer patients [ 90 ], and are known to reduce risk of colorectal cancer development [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of randomized controlled trials (RCTs) examining the feasibility, safety, efficacy, or effectiveness of exercise interventions before, during, and after active oncology treatment across different cancer types have contributed to an ever-growing multitude of systematic reviews and meta-analyses, which in turn have been synthesized in umbrella reviews (2, 3). Such evidence now underpins clinical exercise guideline recommendations, including specific exercise prescriptions for some cancer-related health outcomes (4, 5) and appeals for exercise to be viewed as standard practice in oncology (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many effects within these meta-analyses may be vulnerable to selective (non-) reporting bias, which could change the direction, size, and certainty of pooled effect estimates. The existence of selective (non-) reporting in exercise oncology trials risks undermining exercise-based clinical guidelines and calls to include exercise in the standard care of patients with cancer (6). To date, however, selective (non-) reporting biases have not been assessed in RCTs of exercise interventions for people diagnosed with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The ACSM recently proposed the 'Moving Through Cancer' initiative to increase the proportion of cancer survivors who are physically active [7,8]. This involves healthcare professionals assessing, advising, and referring patients to exercise services.…”
Section: Introductionmentioning
confidence: 99%